Aspek Hukum Tanggung Jawab Orang Tua Terhadap Tindak Kejahatan Dan Perilaku Kriminal Anak Bawah Umur - Mugiono, Mariana; Indradewi, Astrid Athina; Boong, Vicariya Retnowati (Esensi Hukum, 2025)
A minor is under the legal responsibility of their parents or guardians, as regulated in the Civil Code, the Marriage Law, and the Child Protection Law. This responsibility includes the obligation to care for, educate, and supervise the child until they reach adulthood or enter into marriage. In the context of unlawful acts (tort) committed by a child, this research is a normative juridical study using a statutory approach. It highlights the importance of parental supervision and the possibility of exemption from liability if it can be proven that the parents have exercised proper supervision. Through the case involving the child "R", this article emphasizes that parental negligence in supervision may result in legal consequences in the form of compensation obligations to third parties.